TEXT ANALYSIS AND TEXT CREATED IN GRAMMAR LEARNING - Hermawati Syarif (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2015)
The complain of the lecturers on English students’ grammar reflected in their understanding of reading text and their writing product stimulated grammar lecturers to find out the ways to make students use the grammar learned. The paper aims at exploring the learning tasks of text analysis and text created assigned to students of undergraduate level. This activity is the stepping stone to get the rank scale of the clause structure in inductive way. The topics discussed can be in the level of phrase, clause, or clause complex. After comprehending the level of scale structure, the students are directed to identify the rules they have learned by analyzing the text. To use what they have learned, students are assigned to create the text related to the topics. There are various activities that can be done, such as individual, pair-up, or group activities. Practices may be in spoken and written activities. As it was implemented in my grammar class, the result indicates that students were motivated and reflective in using the language. In the low level of structure, such as phrases and simple clause, it worked quite well. It didn’t take much time for the students to analyze the text for the rules and created the text assigned. In clause complex structure, however, it took a little longer for them to do the analysis. But the result is good. It is also a challenge for students to create independent activities outside the class, especially for the bright students.